Health Without Violence In The Digital World: Socialization of Violence Prevention And Physical-Mental Health For High School Students - Ekarisman Ndururu, Bernard; Suwarno, Bambang; Yoana Siregar, Feby; Harmaja, Okta Jaya (CV. Inara, 2025)
Nationwide, school violence and bullying occur. Most instances occur between the first and second years of high school and might be physical (hitting, kicking, or hair pulling) or verbal. Classroom, small group, and computer-based training are provided. After a socialization session, participants were given a questionnaire to learn what they knew and wanted to know about school violence prevention, physical, verbal, and digital violence, early signs of violence, sexual violence, and bullying vs. joking. This socialization report analyzes the pre- and post-test results of training on handling physical, verbal, and online sexual harassment for 67 SMAN 07 Medan students using the Normalized Gain (N-Gain) approach. The Youth Red Cross 006 of SMAN 07 Medan arranged the workshop to study student bullying and physical, verbal, and cyber sexual violence. This research encompasses students from SMAN 7 Medan, specifically from grades X (17), XI (17), and XII (33). Student N-Gain scores increased significantly for male (0.88) and female (0.94) pupils. The training outcomes suggest schools need to hold annual sexual violence and bullying prevention training and outreach initiatives. To maintain student knowledge, schools should incorporate related resources into the curriculum or guidance and counseling. Thus, universities might develop research-based training modules for secondary schools to combat violence and bullying.